2015
DOI: 10.1590/1519-6984.04214
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic variability among different aquatic systems of the central Amazon floodplain during drought and flood events

Abstract: This paper examines water properties from lakes, (depression lakes, sensu Junk et al., 2012), channels (scroll lakes with high connectivity, sensu Junk et al., 2012) and paleo-channels (scroll lakes with low connectivity-sensu Junk et al., 2012, locally called ressacas) located in Mamirauá Sustainable Development Reserve, in Central Amazon floodplain, Amazonas, Brazil. We analysed surface temperature, conductivity, pH, dissolved oxygen, turbidity, transparency, suspended inorganic and organic matter, chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The annual average amplitude of the water level reaches ~10.6 m [31]. In the MSDR lakes, OACs concentrations change seasonally driven by exchange flow (in-and out-flowing) with large fluvial systems, such as the Japurá and Solimões rivers [32]. Few studies reported the bio-optical properties for this Amazon region (e.g., Affonso et al [33]), since most efforts concentrated on multidisciplinary reports about the ecological management, fish communities and ecosystem disturbance [34,35].…”
Section: Site Description and Field Datamentioning
confidence: 99%
“…The annual average amplitude of the water level reaches ~10.6 m [31]. In the MSDR lakes, OACs concentrations change seasonally driven by exchange flow (in-and out-flowing) with large fluvial systems, such as the Japurá and Solimões rivers [32]. Few studies reported the bio-optical properties for this Amazon region (e.g., Affonso et al [33]), since most efforts concentrated on multidisciplinary reports about the ecological management, fish communities and ecosystem disturbance [34,35].…”
Section: Site Description and Field Datamentioning
confidence: 99%
“…Second, the Amazon system can be regarded as a relatively a No biotic factors included; e.g., increased respiration or exudation of DOM. unperturbed river system and is thus especially suited for in situ studies (Furch and Junk, 1997;Devol and Hedges, 2001;Junk et al, 2011;Affonso et al, 2015). Third, intensified biogeochemical processes are expected in the confluence zone due to strong chemical gradients of pH (5-7.5), dissolved organic carbon (3-11 mg/L) and suspended particulate matter (<10-230 mg/L).…”
Section: Introductionmentioning
confidence: 99%
“…and low water), and leads to high spatio-temporal heterogeneity in the aquatic communities (Ward and Stanford, 1995;Ward et al, 1999). The physical and chemical properties of Amazonian floodplain lakes vary widely depending on the seasonal water level fluctuation (Affonso et al, 2015), soil type, vegetation cover, climate conditions (Junk, 2013;Junk et al, 2015), and human land use and occupation (Junk and Cunha, 2012) and can cause increased nutrients leading to high levels of phytoplankton blooms.…”
Section: Introductionmentioning
confidence: 99%